الدين الإسلامي وأثره في معالجة الفساد - الفساد الإداري نموذجاً- - فائز صالح محمود أللهيبي; Fai (University of Mosul-college of Basic Education, 2012)
In the Glorious Quran we find alerting and warnings not to commit corruption and a call for reformation that is located in more than a place in this holy text. Allah has alerted to the necessity of avoiding corruption for its grave consequences on countries and people, besides Allah's direct observance and threat to the corruptors.Corruption has come back in the end of the 1980s as a hot issue in the world agenda that attracts the contemporary states governments and an increasing number of researchers in different fields as well. They wrote a lot on corruption and its relation with development and reform complexities. Thus, a huge amount of knowledge, data, and experiences have accumulated, a matter that was difficult to imagine, a generation before now.